2010
DOI: 10.1155/2010/683875
|View full text |Cite
|
Sign up to set email alerts
|

B7‐H3 and Its Role in Antitumor Immunity

Abstract: B7-H3 is one of the most recently identified members of the B7/CD28 superfamily of costimulatory molecules serving as an accessory modulator of T-cell response. Recently, B7-H3 expression has been reported in several human cancers indicating an additional function of B7-H3 as a regulator of antitumor immunity. However, its precise physiologic role is still elusive, because both stimulatory and inhibitory capacities have been demonstrated. This paper summarizes the available data on B7-H3 in the regulation of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 71 publications
3
100
0
2
Order By: Relevance
“…Increased TAM infiltration has been demonstrated to be associated with poorer prognosis in breast and ovarian cancer (30,31). The present results identified in patients with CRC were consistent with those of previous studies (10,24), and identified that the macrophages that infiltrate CRC tissues may have a harmful role in tumor immune response. The association between B7-H3 expression and expression of CD8 + T cells and CD68 + macrophages was then investigated.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Increased TAM infiltration has been demonstrated to be associated with poorer prognosis in breast and ovarian cancer (30,31). The present results identified in patients with CRC were consistent with those of previous studies (10,24), and identified that the macrophages that infiltrate CRC tissues may have a harmful role in tumor immune response. The association between B7-H3 expression and expression of CD8 + T cells and CD68 + macrophages was then investigated.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, key factors that regulate tumor progression and antitumor immunity are required in the individualized therapy of human CRC. A previous study has demonstrated the clinical significance and regulation of B7-H3 expression in CRC patients (10). In the present study, we investigated the immune cells that infiltrated in CRC, and revealed the mechanism of B7-H3 signaling in the regulation of immune cells in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…B7-H3 protein was also found on various cell types and organs. This broad expression pattern suggests more diverse immunological and probably nonimmunological functions of B7-H3, especially in peripheral tissues (18). Recently, B7-H3 has been Significance Oral squamous cell carcinoma (OSCC) is characterized by high morbidity and mortality, and few therapeutic options.…”
mentioning
confidence: 99%
“…For example, B7-H3 is a member of a family of molecules known to inhibit immune TCR, T-cell receptor [7] reactions and to be upregulated in conditions promoting tumor growth [67]. Upregulation of this molecule in dendritic cells (as observed in NSCLC tumor samples) has been associated with impaired capacity to stimulate T-cell proliferation [68], although recently published data contradicts this finding in murine cancers and other human cancers [69]. Following these observations, strategies to encourage the immune system to recognize tumor antigens and shift the balance away from immune tolerance of tumors are being investigated for NSCLC.…”
Section: Modulation Of Dendritic Cell Phenotype With Recombinant Humamentioning
confidence: 99%